2020
DOI: 10.1007/s10514-019-09899-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative navigation of autonomous GPS-degraded micro air vehicles

Abstract: Many current approaches for navigation of micro air vehicles (MAVs) in GPS-degraded environments use a globally-referenced state for estimation and control, even though this state is not observable when GPS is unavailable. By working with respect to a local reference frame, the relative navigation (RN) framework presented in this paper ensures that the state maintains observability and that the uncertainty remains bounded, consistent, and normally-distributed. RN further insulates flight-critical estimation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…This section is not intended to thoroughly describe all MAV implementation details, but rather to demonstrate that the performance of full-state estimators running on actual hardware parallels the results seen in simulation. Complete details on the relative navigation implementation used for these results, along with a presentation of more extensive flight-test results, are given in [21].…”
Section: Hardware Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This section is not intended to thoroughly describe all MAV implementation details, but rather to demonstrate that the performance of full-state estimators running on actual hardware parallels the results seen in simulation. Complete details on the relative navigation implementation used for these results, along with a presentation of more extensive flight-test results, are given in [21].…”
Section: Hardware Resultsmentioning
confidence: 99%
“…The following sections give highlevel descriptions of the relative front end and global back end. For further details on the RN approach and its implementation, the reader is referred to [20][21][22].…”
Section: Relative Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent simulation results have shown that using the relative navigation framework to ensure observability provides significant advantages in terms of consistency of the estimated relative and global states, as well as some improvement in accuracy and system robustness when incorporating intermittent global information (Wheeler et al, 2018). Furthermore, recent multirotor hardware flight test results have demonstrated the effectiveness of relative navigation for prolonged GPS-degraded navigation of small UASs (Wheeler et al, 2020). This article compliments the work in Wheeler et al (2018) and Wheeler et al (2020) by providing a complete, self-contained, tutorial derivation of the relative state-estimation filter used in those papers to obtain hardware results.…”
Section: Introductionmentioning
confidence: 99%
“…To drive the cost of platforms down, optical sensors in the form of monocular or stereo cameras have been used for obstacle detection and robot control using techniques such as optical flow (Engel, Sturm, & Cremers, ; Horn & Schunck, ; Souhila & Karim, ) or landmark feature extraction for long‐term odometric correction and localization (Goedeme et al., ; Guan et al., ; Klein & Murray, ). Aerial robotics has extended many of these algorithms into three dimensions, including closed‐loop visual navigation and visual‐SLAM (Achtelik, Achtelik, Weiss, & Siegwart, ; Achtelik et al., ; Blösch, Weiss, Scaramuzza, & Siegwart, ; Fraundorfer et al., ; Wheeler & Koch, ; Zingg, Scaramuzza, Weiss, & Siegwart, ) and general sensor fusion for state estimate (Garcia et al., ; López et al., ; Lynen et al., ); the capability to map enclosed buildings (Droeschel et al., ; Shen, Michael, & Kumar, ) has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%